أثر تغير سعر الصرف علي تدفق الاستثما ر الأجنبي المباشر في الجزائر للفترة ) 2010 - 2020 - صنية بديار (My University, 2022)
This research aims to study the relationship between axchange rate changes and foreign direct investment flows in Algeria for the period (2010/2020) Relying on the analytical method of the available data to analyze the interrelation ship between the two variables.the results of the study concluded that the volume of foreign direct investment flows in Algeria is affected by the effects of exchange rate changes by a small percentage because it is not the only factor affecting the volume of foreign direct investment flows in Algeria but there are other factors including: economic. Political regulatory legislative and administrative factors affecting the investment climate in Algeria .................................................... يهدف البحث إلى دراسة العلاقة بين اثر تغيرات سعر الصرف على تدفقات الاستثمار الأجنبي المباشر في الجزائر للفترة) 2010 / 2020 ( بالاعتماد على الأسلوب التحليلي للمعطيات المتاحة لتحليل العلاقة المتبادلة بين المتغيرين, حيث توصلت نتائج الدراسة إلى أن حجم تدفقات الاستثمارات الأجنبية المباشرة في الجزائر تتأثر بتغيرات سعر الصرف بنسبة ضئيلة لان هذا الأخير ليس بالعامل الوحيد المؤثر على حجم تدفقات الاستثمارات الأجنبية المباشرة في الجزائر بل هناك عوامل أخرى منها: عوامل اقتصادية, و سياسية تشريعية, تنظيمية و إدارية مؤثرة بصفة كبيرة على المناخ الاستثماري في الجزائر.